Refinements of some classical inequalities involving sinc and hyperbolic sinc functions - Bagul, Yogesh J.; Thool, Sumedh B.; Chesneau, Christophe; Dhaigude, Ramkrishna M. (Annales Mathematicae Silesianae, 2022)
Several bounds of trigonometric-exponential and hyperbolic-exponential type for sinc and hyperbolic sinc functions are presented. In an attempt to generalize the results, some known inequalities are sharpened and extended. Hyperbolic versions are also established, along with extensions.